Trajectory privacy protection mechanism of obfuscating paths based on vehicles cooperation - Ziwen ZHAO; Ayong YE; Junlin JIN; Lingyu MENG (网络与信息安全学报)
Vehicles sent location information to third parties to obtain location-based services in the Internet of vehicles,which may lead to vehicle trajectory privacy leakage.To address the privacy problem,trajectory privacy protection mechanism of obfuscating paths based on vehicles cooperation was proposed.Firstly,after the vehicle trajectory entropy reaches the custom trajectory protection threshold,the overhead of paths confusion saves by reducing the number of vehicle paths confusion.Then,paths confusion algorithm was designed to increase chances of vehicle paths confusion at intersections,which can improve the degree of vehicle trajectory protection.Finally,the simulation experiment verified the validity and efficiency of the method from the trajectory entropy and trajectory tracking success rate.